Manajemen Program Bimbingan dan Konseling Berbasis Kebutuhan Siswa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article aims to examine the concept and implementation of student-needs-based school counseling program management through a comprehensive review of relevant literature and previous studies. Counseling program management plays a crucial role in providing structured, comprehensive, and responsive guidance services that align with students’ developmental needs. The literature indicates that students’ needs encompass academic, personal-social, and career domains, emphasizing the importance of accurate needs assessment as the foundation of program planning. Numerous studies highlight that counseling programs designed based on students’ actual needs are more effective in enhancing academic motivation, emotional regulation, social adjustment, and career decision-making skills. The synthesis reveals that core management components—planning, organizing, service delivery, and ongoing evaluation—significantly contribute to the effectiveness of counseling services. This review concludes that needs-based counseling program management is the most relevant and impactful approach for improving the quality of school counseling services and supporting students’ holistic development.